HUBUNGAN KEPERCAYAAN DIRI DAN BODY IMAGE PADA WANITA REMAJA DALAM AKTIVITAS OLAHRAGA - Nimrot Manalu; Zia Aulia Milarti Br Ritonga; Royhan Sukri; Gepin Martuah Sinaga; Suwandira; Andes Martua Harahap (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Adolescent girls in sports often experience social pressure that impacts their body perception and self-confidence. Objective: This study investigated the relationship between body perception and self-confidence levels in adolescent girls during sports. Methods: This qualitative research employed a literature review approach by reviewing scientific articles from 2020 to 2025. Results A positive body perception has a significant positive impact on increasing self-confidence by shifting attention from appearance to physical ability. Team sports have been shown to be effective in building self-confidence, while sports that focus on aesthetics have the potential to cause distortions in body perception. In addition, facilities that provide access for everyone and comfortable sportswear have been shown to reduce anxiety and increase engagement. Keywords: Body Image, Self-Confidence, Sport.